Antiamnesic effects of a hydroethanolic extract of crinum macowanii on scopolamine-induced memory impairment in mice - Mugwagwa, Andrew T.; Gadaga, Louis L.; Pote, William; Tagwireyi, Dexter (Hindawi Publishing Corporation, 2016)
Crinum macowanii has been found to contain alkaloids that have activity against acetylcholinesterase enzyme in vitro. The present study was undertaken to investigate the in vivo ability of hydroethanolic crude extract of Crinum macowanii to ameliorate memory impairment induced by scopolamine. Thirty-six male Balb/c mice weighing around 25–35 g were employed in the present investigation. Y-maze and novel object recognition apparatus served as the exteroceptive behavioural models, and scopolamine induced amnesia served as the interoceptive behavioural model. C. macowanii (10, 20, and 40 mg/kg p.o.) was administered in single doses to the mice. Donepezil (3 mg/kg p.o.) was used as a positive control agent. C. macowanii extract reversed the amnesia induced by scopolamine as indicated by a dose-dependent increase in spontaneous alternation performance in the Y-maze task. C. macowanii 40 mg/kg showed significant activity (𝑝 < 0.05 versus negative control), comparable to that of the positive control. C. macowanii also showed memory-enhancing activity against scopolamine-induced memory deficits in the long-term memory novel object recognition performance as indicated by a dose-dependent increase in the discrimination index. The results indicate that the hydroethanolic extract of C. macowanii may be a useful memory restorative mediator in the treatment of cognitive disorders such as Alzheimer’s disease.